If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2x + 1 = 10 Reorder the terms: 1 + x + 2x = 10 Combine like terms: x + 2x = 3x 1 + 3x = 10 Solving 1 + 3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 10 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 10 + -1 3x = 10 + -1 Combine like terms: 10 + -1 = 9 3x = 9 Divide each side by '3'. x = 3 Simplifying x = 3
| (n-5)*9=54 | | 9(x-1)-3=6x+3(-3+x) | | 47-4x=14x+21 | | 28x+91=220 | | 13-9x=68-4x | | x/3-1=x/7+3 | | -(8y+1)-2=8-7y | | 3z-(-1+4z)=-9 | | x-600=50+51 | | v=u-15 | | f(3)=4 | | 107+30x=1007 | | 6x^2-71x+24=0 | | 6x+5y=-32 | | 1/2x-7=14 | | 4(7k+3)=2(4-9k) | | 2(x-8)+2x=4(x+5)-36 | | 71-5x=141 | | -10=-(1+6n)+3n | | (x-6)/14=7x/21 | | 4x-6=20x+9 | | 5(3n-2)=(3n+2)+9 | | x-(-4+3x)=8 | | 2x-301=707 | | 9x+3/2=x | | -8x-3(x+4)=x+7 | | -47=7+6x | | 6x=4(x+1)+2x-6 | | a+b=-2 | | 9=-4(2-7x)-5x | | 3/4(8x-12)=0 | | -4(2-7x)-5x=9 |